2020
DOI: 10.1051/0004-6361/201937131
|View full text |Cite
|
Sign up to set email alerts
|

Exploring open cluster properties with Gaia and LAMOST

Abstract: Context. In Gaia DR2, an unprecedented high level of precision has been reached at sub-milliarcsecond for astrometry and millimagnitudes for photometry. Using cluster members identified with the astrometry and photometry in Gaia DR2, we can obtain a reliable determination of cluster properties. However, because of the shortcomings of Gaia spectroscopic observations in dealing with densely crowded cluster regions, the RVs and metallicity values for cluster member stars from Gaia DR2 are still lacking. It is nec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 63 publications
5
43
1
1
Order By: Relevance
“…The disk metallicity gradients were also studied using LAMOST metallicities of star clusters. 157 By investigating the metallicity separation of actionangle pairs using a large sample of LAMOST dwarf stars, Coronado et al (2020) 158 characterized the dissolution of stellar birth associations into the field.…”
Section: Review Llmentioning
confidence: 99%
“…The disk metallicity gradients were also studied using LAMOST metallicities of star clusters. 157 By investigating the metallicity separation of actionangle pairs using a large sample of LAMOST dwarf stars, Coronado et al (2020) 158 characterized the dissolution of stellar birth associations into the field.…”
Section: Review Llmentioning
confidence: 99%
“…As discussed in Section 4.4.3, OC is a good test bed to check the uncertainties of chemical abundance determinations. Here, we briefly study the uncertainties of chemical abundances estimated by our neural network models using LAMOST-APOGEE common stars as training set of LAMOST cluster members identified by Zhong et al (2020a) and Zhong et al (2020b).…”
Section: The Chemical Abundances Of the Candidates Of Open Cluster Me...mentioning
confidence: 99%
“…We studied kinematics for the clusters using computational algorithm as described by Elsanhoury et al (2018). The line of sight velocities, V r , are given by Zhong et al (2020) as 2.20±5.73 and -33.28±35.30 km s −1 for SAI 44 and SAI 45, respectively. The value of V r for SAI 44 is found to be 7.33±0.05 km s −1 by Carrera et al (2019) while Soubiran et al ( 2018) reported V r values as 11.18±3.21 and -31.02±0.35 km s −1 for SAI 44 and SAI 45, respectively.…”
Section: Dynamical Evolutionmentioning
confidence: 99%